Clinical efficacy of Esmolol, Lignocaine and Diltiazem as premedicant for attenuation of hemodynamic responses of laryngoscopy and endotracheal intubation- a comparative evaluation - Gupta, Chitrangna; Rastogi, Bhawana; Agarwal, Salony; Singh, V. P.; Choudhary, Vineet K.; Inayat, Umar (International Journal of Research in Medical Sciences, 2017)
Background: Direct laryngoscopy and endotracheal intubation after induction of anesthesia is almost always associated with hemodynamic stress response. The aim of this study was to compare esmolol, lignocaine and diltiazem for suppression of laryngoscopy and intubation response. Methods: This randomized prospective double-blind control study was performed on 120 patients of either sex, aged between 18 and 58 years of ASA physical status I and II with Mallampatti grade I and II, undergoing elective surgeries under general anesthesia with endotracheal intubation. Patients were randomized in four groups, Group N (normal saline), Group E (esmolol) 1.5mg/kg I.V, Group D (diltiazem) 0.2mg/kg I.V, and Group L (lignocaine) 1.5mg/kg I.V with 30 patients in each group. Hemodynamic parameters were recorded during the basal period, preinduction, during intubation and at specified intervals. Results: There was significant increase in systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate in the control group (Group N) in association with tracheal intubation. The heart rate was significantly lower in Group E (Esmolol group), followed by Group D (Diltiazem group) and Group L (Lignocaine group). Rate pressure product was significantly lower in group E as compared to other groups, followed by group D and group L. Maximum increase in rate pressure product (RPP) just after laryngoscopy and intubation was ±74.29% in group N, ±16.11% in group E, 25.38% in group D and 38.77%in group L. Conclusions: Esmolol was better than diltiazem and they both were better than lignocaine for preventing the hemodynamic response after laryngoscopy and intubation.